Horrid Henry and the mummy's curse - Simon, Francesca; Ross, Tony. (London : Dolphin, 2003)
"Age Level: 7 and up | Grade Level: 2 to 5 Horrid Henry indulges his favorite hobby--collecting Gizmos; has a bad time with his spelling homework; starts a rumor that there's a shark in the swimming pool; and spooks Perfect Peter with the mummy's curse. Francesca Simon is one of the world's best-loved children's authors. She is the only American to have ever won the Galaxy Book Award, and her creation, Horrid Henry, is the #1 bestselling chapter book series in the UK--with a hit TV show and over fifteen million copies sold! Each book contains four easy-to-read stories and hilarious illustrations by the one and only Tony Ross..." - Lexile Website
H
Originally published: London : Orion Children's, 2000.
b
b
Keywords: Horrid Henry (Fictitious character) -- Juvenile fiction; Boys -- Juvenile fiction; Disorderly conduct -- Juvenile fiction